“APBD YANG DIPERCAYA,” REBRANDING KEUANGAN DAERAH YANG KREDIBEL―PENGALAMAN NEGARA-NEGARA EROPA - Rostamaji Korniawan (UPT Penerbitan Universitas Jember)
Regional Government Budget as regional financial product needs a new approach to be understandable and acceptable by the public in such region. To make it accepted by the public, this review aimed to build a concept of acceptable regional financial product. The concept was built by rebranding the Regional Government Budget in order to attract the public’s trust. Such rebranding was done by communicating “the trusted Regional Government Budget” amid regional people. By communicating the branding of effective regional financial product, it was expected that local public’s thought could change their own behaviors. In analyzing the rebranding of the Regional Government Budget offerred to the Regional Government, this review was using literature review approach which was done systematically. The Regional Government has capacity to develop the rebranding process, especially to improve the performance of the Regional Government Budget through the excellences of the region.